An investigation of winter minimum temperatures in the mountains of Montenegro – a case study from the karst depression of Valoviti Do and selected mountain stations of northern Montenegro - Ogrin, Matej; Nikolić, Gojko; Ogrin, Darko; Trobec, Tajan (Geographica Pannonica, 2018)
This article presents the findings from measurements of winter minimum temperatures taken over a period of several years in the high mountain karst depression of Valoviti Do on the Durmitor massif (Montenegro), and compares them with temperatures measured in the network of official stations operated by the Montenegro Hydrometeorological Institute. We took into consideration meteorological stations that are located in the coldest sites of Montenegro. The results of the measurements showed that winter minimum temperatures in high mountain depressions of Montenegro are considerably lower than the temperatures measured in the framework of the national network of meteorological stations, which are rarely located in the mountain environment. In the course of taking measurements in five nonconsecutive winter seasons in the period from 2007 to 2015 we also measured the lowest temperature recorded to date in Montenegro, -40 ºC.